Advanced‐Stage Parkinson's Disease: From Identification to Characterization Using a Nationwide Database. Issue 4 (29th April 2022) - Barer, Yael; Gurevich, Tanya; Chodick, Gabriel; Giladi, Nir; Gross, Ruth; Cohen, Raanan; Bergmann, Lars; Jalundhwala, Yash J.; Shalev, Varda; Grabarnik‐John, Meital; Thaler, Avner
ABSTRACT: Background: As Parkinson's disease (PD) progresses, response to oral medications decreases and motor complications appear. Timely intervention has been demonstrated as effective in reducing symptoms. However, current instruments for the identification of these patients are often complicated and inadequate. It has been suggested that anti‐PD intensified therapy (IT) can serve as a proxy for increased burden of disease. Objective: To explore whether IT aligns with events reflecting advanced PD (APD) burden. Methods: This was a retrospective analysis of PD beneficiaries in the second‐largest healthcare provider in Israel. Patients with PD diagnosed between January 2000 and June 2018 and treated with levodopa (l ‐dopa) ≥5 times/day and/or ≥1000 mg l ‐dopa equivalent daily dose were defined as the IT cohort (n = 2037). Treated patients with PD not fulfilling this criterion were defined as the nonintensified therapy (NIT) cohort (n = 3402). Point prevalence and 5‐ and 10‐year cumulative incidence of IT were assessed. Baseline demographic and comorbidities, 1‐year healthcare resource use, health costs, and time to clinical events were assessed and compared between cohorts. Results: IT was associated with significantly ( P  < 0.05) higher healthcare resource use compared with NIT. In turn, IT patients incurred higher healthcare costs ( P  < 0.001) and were at greater risk for mortality, hospitalization, disability, and device‐aided therapy use ( P  < 0.001, for all comparisons). Conclusions: Treatment intensity can serve as an objective and robust indicator of more APD. This readily extractable marker can be easily integrated into electronic medical record alerts to actively target more advanced patients and to guide risk‐appropriate care.